Prospect theory : for risk and ambiguity - Wakker, Peter P., 1956- (Cambridge, UK ; New York : Cambridge University Press, 2010)
"Prospect Theory: For Risk and Ambiguity provides the first comprehensive and accessible textbook treatment of the way decisions are made both when we have the statistical probabilities associated with uncertain future events (risk) and when we lack them (ambiguity). The book presents models, primarily prospect theory, that are both tractable and psychologically realistic. A method of presentation is chosen that makes the empirical meaning of each theoretical model completely transparent. Prospect theory has many applications in a wide variety of disciplines. The material in the book has been carefully organized to allow readers to select pathways through the book relevant to their own interests. With numerous exercises and worked examples, the book is ideally suited to the needs of students taking courses in decision theory in economics, mathematics, finance, psychology, management science, health, computer science, Bayesian statistics, and engineering"--
Introduction -- Expected utility. The general model of decision under uncertainty no-arbitrage (expected utility with known utilities and unknown probabilities) -- Expected utility with known probabilities--'risk'--and unknown utilities -- Applications of expected utility for risk -- Expected utility with unknown probabilities and unknown utilities -- Nonexpected utility for risk. Heuristic arguments for probabilistic sensitivity and rank dependence -- Probabilistic sensitivity and rank dependence analyzed -- Applications and extensions of rank dependence -- Where prospect theory deviates from rank-dependent utility and expected utility: reference dependence versus asset integration -- Prospect theory for decision under risk -- Nonexpected utility for uncertainty. Extending rank-dependent utility from risk to uncertainty -- Ambiguity: where uncertainty extends beyond risk -- Prospect theory for uncertainty -- Conclusion.
Includes bibliographical references (pages 461-491) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Decision making; Risk; Uncertainty; Probabilities; Decision Making; Risk; Probability; Prise de décision.; Risque; Incertitude; Probabilités.; decision making; probability; BUSINESS & ECONOMICS -- Economics -- Microeconomics; Prise de décision.; Analyse des risques; Probabilités.; Modèles mathématiques.; Manuels; Decision making; Probabilities; Risk; Uncertainty; Decision making; Risk; Uncertainty; Probabilities; Évaluation du risque; Incertitude (économie politique); Prise de décision.; Probabilités.; Beslutsfattande; Risk -- ekonomiska aspekter; Sannolikhet; Beslutsteori; Electronic book